2023
DOI: 10.1021/acs.langmuir.2c03181
|View full text |Cite
|
Sign up to set email alerts
|

Cell Membrane Oscillations under Radiofrequency Electromagnetic Modulation

Abstract: Cell responses to external radiofrequencies (RF) are a fundamental problem of much scientific research, clinical applications, and even daily lives surrounded by wireless communication hardware. In this work, we report an unexpected observation that the cell membrane can oscillate at the nanometer scale in phase with the external RF radiation from kHz to GHz. By analyzing the oscillation modes, we reveal the mechanism behind the membrane oscillation resonance, membrane blebbing, the resulting cell death, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 62 publications
(120 reference statements)
0
7
0
Order By: Relevance
“…16 Research results demonstrate a moderate increase in the integral temperature of the cellcontaining media of at most 10 °C over a treatment time of 10 min, 16 suggesting that the temperature itself is not a major factor in the sensitization effect. However, the described EM effect of the DT emitting in the kHz range 17 on cancer cells was achieved when the cell culture was placed in the immediate vicinity (few millimeters) from the upper flange of the DT, while for real applications, a more distant (at several centimeters) effect is desirable. It was found experimentally 17 that the discharge frequency in the kHz range causes cell membrane oscillation also in the kHz range, and one can expect that this effect should persist at some distance from the discharge region where the electric field is still intensive enough.…”
Section: ■ Introductionmentioning
confidence: 99%
“…16 Research results demonstrate a moderate increase in the integral temperature of the cellcontaining media of at most 10 °C over a treatment time of 10 min, 16 suggesting that the temperature itself is not a major factor in the sensitization effect. However, the described EM effect of the DT emitting in the kHz range 17 on cancer cells was achieved when the cell culture was placed in the immediate vicinity (few millimeters) from the upper flange of the DT, while for real applications, a more distant (at several centimeters) effect is desirable. It was found experimentally 17 that the discharge frequency in the kHz range causes cell membrane oscillation also in the kHz range, and one can expect that this effect should persist at some distance from the discharge region where the electric field is still intensive enough.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It is the basic assumption of the model that charge is bound to the membrane and membrane deformation is coupled with the charge motion. It was also observed that as a result of the resonance these oscillations lead to membrane damage and cavitation near the membrane [29].…”
Section: Adaptive Plasmas and Plasma Modalitiesmentioning
confidence: 98%
“…Recent interferometric measurements of cell membrane oscillations under electromagnetic fields were performed [29]. Nanometer-scale cell membrane oscillation in-phase with an external electric field were demonstrated.…”
Section: Adaptive Plasmas and Plasma Modalitiesmentioning
confidence: 99%
“…The simulations presented in this paper indicates that the plasma oscillation power density is playing the major role in the GHz emissions, while the bulk current and the bremsstrahlung emissions have neglectable power. Meanwhile, in other studies, it has been shown that the discharge frequency of plasma has significant physical effects in plasma biomedical applications, such as the sensitization and cell membrane damage [17,41], not only for the cancerous cells, but also for the blood cells and skin tissues according to some recent studies [42,43]. However, the exact physical effects of the GHz emissions are still unknown.…”
Section: The Physical Dose Of Plasma Medicinementioning
confidence: 99%
“…The second one is at the plasma jet's discharge frequency, which is the repetition of the impact of the high-voltage streamer head at kHz frequency [16]. The cells' response to the kHz effects was recently observed by Lin et al using a laser Michelson interferometer [17]. The cell membrane oscillates under such an emission due to the membrane potential, and the in-situ damage leads to blebbing and finally both apoptosis and necrosis [17] which agrees with other previous observations [8,11].…”
Section: Introductionmentioning
confidence: 96%